Levator Resection in Neurogenic Ptosis Oculi Sinistra et causa Third Nerve Paresis + Type II Diabetes: A Case Report: Poster Presentation - Case Report - Resident - Retno Tharra Handayani; Riani Erna (Majalah Oftalmologi Indonesia, 2023)
Introduction : Neurogenic ptosis is abnormal position of the upper eyelid caused by dysfunction or damage to the oculomotor or sympathetic nerves supplying the eyelids. Third nerve palsy (35.7%) is the most common cause among others. We report a case of neurogenic ptosis managed surgically by levator resection. Case Illustration : A 67-year-old male complained of drooping left upper eyelid, getting worse in 7 months. He had history of falling off motorcycle 6 months ago. Clinical histories of hypertension and diabetes mellitus were found. Right and left eyelids measurements in millimeter showed horizontal palpebral fissure (HPF) 28/26, vertical palpebral fissure (VPF) 6/3, margin reflex distance 1 (MRD1) 2/-2, margin reflex distance 2 (MRD2) 6/5, margin limbal distance (MLD) 8/4, and levator function (LF) 8/3. Bell’s phenomenon was negative in both eyes. Ice pack test was negative. There were ocular movement restriction in his left eye. Patient underwent a maximum levator resection and had better levator function after 3 weeks follow up. Discussion : Neurogenic ptosis caused by third nerve injury is associated with microvascular ischemia such as diabetes mellitus and hypertension. Operative management is carried out after 3 to 6 months observation. Evaluation of levator function allows the clinician to correctly classify the degree and type of ptosis. Maximal levator resection is the treatment of choice for ptosis with poor levator function. Conclusion : Although various surgical techniques have been developed, ptosis correction should be performed according to the indications and clinical condition of the patient.